WALI `ADHOL FROM THE PERSPECTIVE OF INDONESIAN POSITIVE LAW AND ITS PRACTICE IN RELIGIOUS COURTS - Salamah, Ade (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
Marriage in Islamic law plays a vital role for individuals and society, with the guardian (wali) being one of the essential pillars for the marriage to be valid. However, issues can arise in practice when the designated guardian, particularly the father, refuses to fulfill his duty, a situation known as wali adhol. This article discusses the importance of the guardian's role in Islamic marriage, the legal and social problems caused by wali adhol, and the solutions provided by Indonesia's legal system, including the appointment of a judge guardian to replace a guardian who refuses or cannot be present. In this context, the Compilation of Islamic Law (KHI) and Minister of Religious Affairs Regulation No. 22 of 2024 provide the legal basis for the religious court to appoint a judge guardian in wali adhol cases. The article also explores the differing views among Islamic schools of thought on wali adhol and how Indonesia's religious courts play a key role in ensuring the validity of the marriage despite challenges posed by the guardian. This study concludes that while wali adhol presents challenges, Indonesia's legal system offers clear mechanisms to address this issue, ensuring fairness and the successful implementation of lawful marriages in accordance with Islamic principles.